6-OHDA-Induced Changes in Colonic Segment Contractility in the Rat Model of Parkinson's Disease. (27th January 2023) - Murillo, Maria Del Pilar; Johansson, Ebba; Bryntesson, Victoria; Aronsson, Patrik; Tobin, Gunnar; Winder, Michael; Carlsson, Thomas
Abstract : Background . Gastrointestinal dysfunction is one of the most common non-motor symptoms in Parkinson's disease (PD). The exact mechanisms behind these symptoms are not clearly understood. Studies in the well-established 6-hydroxydopamine (6-OHDA) lesioned rats of PD have shown altered contractility in isolated circular and longitudinal smooth muscle strips of distal colon. Contractile changes in proximal colon and distal ileum are nevertheless poorly studied. Moreover, segments may serve as better tissue preparations to understand the interplay between circular and longitudinal smooth muscle. This study aimed to compare changes in contractility between isolated full-thickness distal colon muscle strips and segments, and extend the investigation to proximal colon and distal ileum in the 6-OHDA rat model. Methods . Spontaneous contractions and contractions induced by electrical field stimulation (EFS) and by the non-selective muscarinic agonist methacholine were investigated in strip and/or segment preparations of smooth muscle tissue from distal and proximal colon and distal ileum in an in vitro organ bath comparing 6-OHDA-lesioned rats with Sham-operated animals. Key Results . Our data showed increased contractility evoked by EFS and methacholine in segments, but not in circular and longitudinal tissue strips of distal colon after central 6-OHDA-induced dopamine denervation. Changes in proximal colon segments were also displayed in high K + Krebs-induced contractility and spontaneous contractions. Conclusions . This study further confirms changes in smooth muscle contractility in distal colon and to some extent in proximal colon, but not in distal ileum in the 6-OHDA rat model of PD. However, the changes depended on tissue preparation.